2022
DOI: 10.46754/jssm.2022.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Activity, Total Phenolic and Flavonoid Contents of Malaysian Stingless Bee Propolis Extracts

Abstract: This study aims to determine the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of ethanolic extract propolis (EEP) and water extract propolis (WEP) derived from six Malaysian stingless bee species. The TPC and TFC were measured by Folin-Ciocalteu colorimetric and aluminium chloride methods, respectively. The antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The results indicated that EEP of Geniotrigona thoracica ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Studies have shown that the antibacterial activity of propolis corresponds to its polyphenolic compounds such as phenolic acid and flavonoids (Abdelrazeg et al, 2020). Furthermore, Adli et al (2022) demonstrated that the EEP of H. itama possessed higher total phenolic and flavonoid contents compared to WEP. Similar findings were reported by Kubiliene et al (2015) and Abdullah et al (2019) who indicated that propolis extracted using alcohol and methanol yielded better antimicrobial activity compared to water extract propolis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that the antibacterial activity of propolis corresponds to its polyphenolic compounds such as phenolic acid and flavonoids (Abdelrazeg et al, 2020). Furthermore, Adli et al (2022) demonstrated that the EEP of H. itama possessed higher total phenolic and flavonoid contents compared to WEP. Similar findings were reported by Kubiliene et al (2015) and Abdullah et al (2019) who indicated that propolis extracted using alcohol and methanol yielded better antimicrobial activity compared to water extract propolis.…”
Section: Discussionmentioning
confidence: 96%
“…The colonies were housed in wooden nest boxes under the shade with predominant vegetation consisting of Lamiaceae, Myrtaceae, Rubiaceae, Fabaceae, Lythraceae, Scrophulariaceae, Elaeocarpaceae, Sapindaceae, Moraceae, and Anacardiaceae. The stingless bee species was identified by an entomologist from the Centre for Insect Systematics (CIS), Universiti Kebangsaan Malaysia with the accession number CIS-TRI-2022-02 (Adli et al, 2022). The propolis sample was collected by scraping the inside of the hives using a clean stainless-steel spatula.…”
Section: Propolis Collectionmentioning
confidence: 99%
“…On the other hand, the presence of FLAV compounds in propolis samples can positively influence the quantification of TPC in all tested methods. Several works show that there is a positive correlation between TPC and flavonoid content [ 60 , 61 ]. However, no comparative work has been found relating TPC to HBA and HCA content.…”
Section: Discussionmentioning
confidence: 99%